1993
DOI: 10.1002/ajh.2830440110
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous demonstration of the Philadelphia chromosome in T, B, and myeloid cells

Abstract: A patient presented with lymphoblastic lymphoma in lymph-nodes and chronic myelogenous leukemia (CML) in narrow and peripheral blood. All marrow and unstimulated peripheral blood cells contained the Philadelphia chromosome[t(9:22)]. Lymphoma cells were analyzed by flow cytometry and were identified as T cells (CD2+CD5+CD7+CD34+). All fresh lymphoma cells contained the t(9:22) translocation. Cultures of purified peripheral blood T and B cells and specifically stimulated NK cells revealed that 59% of the B cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…Similar results for T lymphocytes were achieved using CD4 or CD8 antibodies. These results do not support the hypothesis that T cells are not, or only in a very small number, involved in the malignant transformation because of their long life-span (MacKinney et al, 1993;Kearney et al, 1982;Bartram et al, 1987). Due to their rarity in CML, we were able to investigate only a few plasma cells with the combination of MGG and FISH or with FICTION using CD38 þ cells with the typical morphology of plasma cells.…”
Section: Discussionmentioning
confidence: 74%
“…Similar results for T lymphocytes were achieved using CD4 or CD8 antibodies. These results do not support the hypothesis that T cells are not, or only in a very small number, involved in the malignant transformation because of their long life-span (MacKinney et al, 1993;Kearney et al, 1982;Bartram et al, 1987). Due to their rarity in CML, we were able to investigate only a few plasma cells with the combination of MGG and FISH or with FICTION using CD38 þ cells with the typical morphology of plasma cells.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, the Ph chromosome is found in all hematopoietic lineages. [3][4][5][6][7][8] Despite this, in the chronic phase (CP) of CML, leukemic stem cells can differentiate, and mature neutrophils dominate the peripheral blood and bone marrow. Therefore, it follows that BCR-ABL preferentially promotes granulocytic differentiation and Ph-positive leukemic stem cell proliferation, possibly through the constitutive expression of growth-stimulating factors by leukemic progenitors and through the anti-apoptotic properties of CML cells.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, although very little is known about the exact lifespan of NK cells (Pabst and Westermann, 1993), Little et al (1962) have reported that turnover times of small lymphocytes which are supposed to be T and B cells in peripheral blood are longer than large lymphocytes, which are supposed to be NK cells in rats. MacKinney et al (1993) also pointed out that T lymphocytes have a longer lifespan than B and NK cells.…”
Section: Discussionmentioning
confidence: 96%